Development of A Village-Based Organic Vegetable Business Model Using The Business Model Canvas For Sustainability (BMCS) - Pranatasari, Nur Army; Hardjomidjojo, Hartrisari; Machfud (Indonesian Journal of Business and Entrepreneurship, 2025)
Background: Business model changes have far-reaching implications for overall company performance, including social and environmental aspects. Business Model Canvas (BMC) is often used as a framework for designing business models. However, the concept of sustainability involving social and environmental aspects is often not fully integrated into using BMC. In other words, BMC tends to focus more on economic aspects alone. Urban studies have dominated research on business and entrepreneurship. Studies on rural entrepreneurship, especially in developing countries, are still minimal, with 78% (10 documents) of journal article publications in 2021 dominated by social sciences (26%), business, management, accounting (19%), and agriculture and biology (7%). In addition, there is a research gap in economics, especially regarding the role of women in organic farming, although women are more often involved in organic farming than men. Purpose: This research uses the Business Model Canvas for Sustainability (BMCS) to develop a business model centered on village-based sustainability issues, specifically focusing on the Mekar Sari Women Farmers Group (WFG) in Bogor, Indonesia. Design/methodology/approach: The research was conducted in Neglasari Village, Bogor District, West Java, Indonesia. The research was conducted for 3 months for one case study from July to September 2024. The sampling technique used was purposive sampling with a descriptive-qualitative approach. The research used primary and secondary data from literature studies, field observations, and interviews with 20 respondents selected based on the criteria set. It was then analyzed with the business unit’s BMCS framework, the results of which were used to identify the 10 main elements of BMCS. Finding/Result: The results showed that the Mekar Sari Women Farmers Group business had implemented most of the BMCS components. Elements identified include vision and mission, value propositions, customer segments, competitors, stakeholders, revenue model, key resources, key activities, key partnerships, and cost structures. Conclusions: Based on the identification of the business model currently implemented by WFG Mekar Sari, it shows that WFG has constraints on market competition, customer segments, and key partnerships that affect the revenue model of Mekar Sari’s WFG organic vegetable business. To improve business performance, WFG Mekar Sari needs to adopt a sustainable business strategy for its future business development. Originality/value (State of the art): This study contributes to developing sustainable business models by addressing the gap in integrating sustainability into the BMC framework, especially in village-based businesses. This study shows that BMCS is one of the tools that can be considered for designing more sustainable businesses. Keywords: BMCS, business model, organic vegetables, sustainability, women farmer group (WFG)